Evaluation of osteoarthritic features in peripheral joints by ultrasound imaging: A systematic review. Issue 3 (September 2021) - Molyneux, Prue; Bowen, Catherine; Ellis, Richard; Rome, Keith; Frecklington, Mike; Carroll, Matthew
Abstract: Objective: To determine how structural and inflammatory osteoarthritis (OA) features in peripheral joints are assessed, defined and graded by ultrasound (US) imaging. Design: MEDLINE, CINAHL, Cochrane and SPORTDiscus were systematically searched in March 2021. To be eligible, studies needed to (1) include participants with peripheral joint OA, and (2) used grey scale USI or power Doppler (PD) to assess one or more US features in peripheral joints of the hands and feet. Methodological quality of all included studies was assessed using the Critical Appraisal Skills Program (CASP) tool. Results: A total of 159 citations were identified for screening. Thirty-two articles were included for final analysis and were of good methodological quality. Thirty articles evaluated US features of hand OA and two assessed US OA features in the foot. There were inconsistencies between studies in terms of what US features were assessed, how these features were defined and what grading system was applied to determine degree of osteoarthritic change. Conclusion: The review found inconsistencies in the definition of synovial pathology. Consequently, it is unclear whether synovial pathology is best represented as separate entities or combined as a single domain, termed "synovitis". How OA US features were defined and graded has largely been extrapolated from recommendations originally constructed for populations with rheumatoid arthritis (RA). Given the prognostic value of synovitis for OA progression and the reduced degree of inflammation experienced in OA compared to RA, the validity of applying definitions, grading systems and atlases originally developed for inflammatory arthritis needs consideration.